2008 Computers in Cardiology 2008
DOI: 10.1109/cic.2008.4749099
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of possible necrotic-core artifact around dense calcium in Virtual Histology images

Abstract: Virtual Histology (VH) is a new medical imaging technique that allows the assessment of atherosclerotic plaque composition, a potential useful tool for the evaluation of individuals with coronary disease. Empirical observation has suggested that plaque areas adjacent to dense calcium (DC) are frequently coded as necrotic core (NC) in VH images. The main objective of the study was to evaluate whether the presence of DC induces an artifactual coding of NC in adjacent structures. To test this effect, a set of 89 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…This phenomenon was caused by similarities between NC and CA in gray-level IVUS images. This fact supports the previous studies, which have shown that plaque areas adjacent to dense calcium are frequently coded as necrotic tissue in VH images (Sales et al, 2008). By considering selected cross-sections that contained plaque areas with a homogeneous tissue composition as reported in (Gonzalo et al, 2008), the accuracy results can be increased significantly.…”
Section: Nosupporting
confidence: 85%
“…This phenomenon was caused by similarities between NC and CA in gray-level IVUS images. This fact supports the previous studies, which have shown that plaque areas adjacent to dense calcium are frequently coded as necrotic tissue in VH images (Sales et al, 2008). By considering selected cross-sections that contained plaque areas with a homogeneous tissue composition as reported in (Gonzalo et al, 2008), the accuracy results can be increased significantly.…”
Section: Nosupporting
confidence: 85%